2021
DOI: 10.1016/j.jamcollsurg.2020.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented Care in the Treatment of Rectal Cancer and Time to Definitive Therapy

Abstract: BACKGROUND: The National Accreditation Program for Rectal Cancer (NAPRC) emphasizes a multidisciplinary approach for treating rectal cancer and has developed performance measures to ensure that patients receive standardized care. We hypothesized that rectal cancer patients receiving care at multiple centers would be less likely to receive timely and appropriate care. STUDY DESIGN: A single institution retrospective review of a prospectively maintained d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…4 Division of Cancer Control and Policy, National Cancer Control Institute, National Cancer Center, Gyeonggi-do, Goyang-Si, Republic of Korea. 5 Department of Information and Statistics, RINS, Gyeongsang National University, 501 Jinju-daero, Jinju-si, Gyeongsangnam-do, South Korea.…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Division of Cancer Control and Policy, National Cancer Control Institute, National Cancer Center, Gyeonggi-do, Goyang-Si, Republic of Korea. 5 Department of Information and Statistics, RINS, Gyeongsang National University, 501 Jinju-daero, Jinju-si, Gyeongsangnam-do, South Korea.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Patients with cancer commonly receive fragmented cancer care, which is defined as undergoing treatment across multiple healthcare facilities [3][4][5]. Previous studies have demonstrated that fragmented cancer care is associated with a reduction in overall survival, high healthcare costs, unnecessary treatments, increased time to treatment, and inferior quality of care [3,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The management of individuals with rectal cancer often requires several diagnostic tests, the use of multidisciplinary teams during the delivery of multimodality treatment, and ongoing surveillance for identifying recurrent or metastatic disease. With this level of complexity, the fragmentation of care can occur [ 3 ], and inconsistent delivery of treatments may be observed [ 4 ]. In addition, due to the nature of the treatments, patients with rectal cancer often experience high rates of short- and long-term morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…This pathway can lead to poor compliance and healthcare disparities since it can be particularly burdensome for patients with lower health literacy, limited expenses for travel, or inability to take off time from work. Recent work has also shown that “fragmented” rectal cancer care across multiple institutions can lead to delays in treatment [ 1 ].…”
Section: Introductionmentioning
confidence: 99%